Sprouting Time Affects Sorghum (Sorghum bicolor [L.] Moench) Functionality and Bread-Baking Performance - Gaetano Cardone; Rubina Rumler; Sofia Speranza; Alessandra Marti; Regine Schönlechner (Foods, 2021)
Despite being considered a climate-resilient crop, sorghum is still underutilized in food processing because of the limited starch and protein functionality. For this reason, the objective of this study was to investigate the effect of sprouting time on sorghum functional properties and the possibility to exploit sprouted sorghum in bread making. In this context, red sorghum was sprouted for 24, 36, 48, 72, and 96 h at 27 °C. Sprouting time did not strongly affect the sorghum composition in terms of total starch, fiber, and protein contents. On the other hand, the developed proteolytic activity had a positive effect on oil-absorption capacity, pasting, and gelation properties. Conversely, the increased α-amylase activity in sprouted samples (≥36 h) altered starch functionality. As regards sorghum-enriched bread, the blends containing 48 h-sprouted sorghum showed high specific volume and low crumb firmness. In addition, enrichment in sprouted sorghum increased both the in vitro protein digestibility and the slowly digestible starch fraction of bread. Overall, this study showed that 48 h-sprouted sorghum enhanced the bread-making performance of wheat-based products.